1980
DOI: 10.1007/bf00421352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strength training and immobilization on human muscle fibres

Abstract: Seven healthy male subjects were studied under control conditions and following 5-6 months of heavy resistance training and 5-6 weeks of immobilization in elbow casts. Cross-sectional fibre areas and nuclei-to-fibre ratios were calculated from cryostat sections of needle biopsies taken from triceps brachii. Training resulted in a 98% increase in maximal elbow extension strength as measured by a Cybex dynamometer, while immobilization resulted in a 41% decrease in strength. Both fast twitch (FT) and slow twitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
103
1
24

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(148 citation statements)
references
References 26 publications
20
103
1
24
Order By: Relevance
“…The type I fibers belong to motor units which are the first to be recruited during repetitive movements of relativelylow tension (21). The larger area of the fibers in the patient biopsies, obtained from tender points, may reflect an adaptive response to frequent occupational use of this region of the muscle since muscular usage might cause an increase in fiber area (35,36). However, one might then expect the fiber size to be normalized in the patients since they had been on sick leave for a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The type I fibers belong to motor units which are the first to be recruited during repetitive movements of relativelylow tension (21). The larger area of the fibers in the patient biopsies, obtained from tender points, may reflect an adaptive response to frequent occupational use of this region of the muscle since muscular usage might cause an increase in fiber area (35,36). However, one might then expect the fiber size to be normalized in the patients since they had been on sick leave for a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Isometric strength training of this type for [5][6][7][8][9][10][11][12] weeks produces increases in maximal force of 20 40 o (McDonagh, Hayward & 1)avies, 1983;Komi, Viitasalo, Rauramaa & Vihko, 1978). However, the increase in the cross-sectional area of whole muscle (Ikai & Fukunaga, 1970) and of single muscle fibres (MacDougall, Elder, Sale, Moroz & Sutton, 1980) is only one-quarter of the increase in the maximal voluntary contractile force (m.v.c). This is surprising, as muscle force should be directly proportional to the cross-sectional area of the muscle.…”
Section: Introductionmentioning
confidence: 99%
“…There is no known mechanism for memory in muscle cells, and, to date, the longlasting effects of previous training have been attributed to motor learning in the central nervous system (3). However, it has been reported that muscles can remain hypertrophic after several months of detraining (1,(4)(5)(6)(7)(8). In one study on elderly individuals who had strength-trained, force was still 9-14% higher even after 2 y of detraining (7).…”
mentioning
confidence: 99%